ChemInform Abstract: Metal‐Free Intramolecular Alkyne‐Azide Cycloaddition to Construct the Pyrazolo[4, 3‐f][1, 2, 3]triazolo[5, 1‐c][1, 4]oxazepine Ring System. Issue 52 (10th December 2015) - Arbaciauskiene, Egle; Laukaityte, Vaida; Holzer, Wolfgang; Sackus, Algirdas
Abstract: A simple and efficient synthetic route to a new pyrazolotriazolooxazepine ring system is developed by employing a metal‐free, intramolecular alkyne‐azide cycloaddition reaction as the key step.